TINDAKAN PEMERINTAH DAERAH KABUPATEN KEPULAUAN MERANTI DALAM PELESTARIAN PARIWISATA PERANG AIR 2016-2018 - Restu Prayogi; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Water War Tourism is one of the attractions in the Meranti Islands Regency. Water War Tourism Object is a tourist attraction derived from the habits of coastal communities in the Meranti Islands Regency, but in its development at this time the water war tourism event has been managed by the Regional Government of the Meranti Islands Regency, so it has undergone many changes. The water war tourism event has the potential to be developed so that it will increase a big role for regional income, but in the tourism sector developed by the government not only to generate regional income, but also in the preservation of water war tourism carried out by the Meranti Islands regional government. guarantees to tourists who attend the war water tourism. The formulation of the problem of this research is How the Government of the Meranti Islands Regency in preparing social security for every tourist who came to take part in the water war in the Meranti Islands Regency 2016-2018?. This study aims to describe the government's actions in terms of regulation, structuring community norms in the preservation of water war tourism in the Meranti Islands District 2016-2018. This research uses a qualitative approach with the type of descriptive approach. Data collection techniques used were interviews and documentation. Data analysis is performed if the empirical data obtained is in the form of a tangible collection of words and not a series of numbers. The results of this study are the actions of the local government on the preservation of water war tourism in the Meranti Islands Regency as an effort to provide guarantees and protections for tourists who take part in the water war tourism event can be done by providing facilities such as accommodation and infrastructure, but in accommodation accommodation facilities are still not running optimally this is due to the inadequate capacity of the hotel then in an effort to provide a sense of security to tourists The Regional Government of the Meranti Islands Regency coordinates with the security and community organizations. Keywords: Government Actions, Guarantees, Protection